Novel High Oxygen Affinity Hemoglobin Variant in a Patient with Polycythemia: Hb Kennisis [β85(F1)Phe→Leu (TTT>TTG); HBB: c.258T>G]. (2nd January 2020) - Nabhani, Ibrahim Al; Aneke, John C.; Verhovsek, Madeleine; Eng, Barry; Kuo, Kevin H.M.; Rudinskas, Leona C.; Waye, John S.
Abstract: We report the case of a 61-year-old Canadian male of Maltese descent investigated for unexplained polycythemia. Decreased p50 suggested the presence of a high oxygen affinity hemoglobin (Hb) variant. Molecular genetic testing demonstrated that he carries a novel missense mutation ( HBB : c.258T>G), resulting in a Phe→Leu substitution at position 85 of the β chain. The novel Hb variant has been designated Hb Kennisis in recognition of where the proband resides. Two other missense mutations have been reported at this position [Hb Bryn Mawr or Hb Buenos Aires, β85(F1)Phe→Ser ( HBB : c.257T>C); Hb Grantham, β85(F1)Phe→Cys; ( HBB : c.257T>G)], both of which have increased oxygen affinity.